Adapting to climate change through disaster risk reduction in the Caribbean: lessons from the Global South in tackling the Sustainable Development Goals - Jerez Columbi?, Yairen (Palgrave Macmillan, Springer, 2022)
Developing resilience in conditions of extreme geographic and economic vulnerability, Small Island Developing States (SIDS) have learned to share what works for adaptation on the ground through transnational Disaster Risk Reduction initiatives that address the Sustainable Development Goals (SDGs). This chapter focuses on South-South Cooperation between Caribbean SIDS on Climate Change Adaptation and Disaster Risk Management, as well as triangulation with the European Union and international organisations through the African, Caribbean and Pacific-European Union Natural Disaster Risk Reduction (ACP-EU NDRR) Program. It critically analyses collaborations between regional platforms to show evidence of successful transferable adaptation strategies and tools that have emerged from disaster risk management experiences. Acknowledging the SIDS’ contribution to climate change adaptation is key for advancing both research and action. The examples of South-South cooperation between SIDS and triangulation with Europe and international organisations addressed in this chapter show that a coherent and effective theoretical framework for impactful adaptation research and global climate action should bring forward participatory, transdisciplinary and translocal perspectives informed by the experiences of early adaptors in the Global South.
Creating Resilient Futures: Integrating Disaster Risk Reduction, Sustainable Development Goals and Climate Change Adaptation Agendas
PUBLISHED
Keywords: Regional; Collaboration; Environmental; Justice; Action; Identities in Transformation; Inclusive Society; International Development; International Integration; Smart & Sustainable Planet; CLIMATE CHANGE; Caribbean Studies; Caribbean?Europe relations; Climate Change Impacts on the Environment; Inter-disciplinary approaches to International Relations; Interdisciplinary research; Latin American and Caribbean Studies; Latin America?Europe relations; Postcolonialism and the Caribbean; Sustainable Development; UN Sustainable Development Goals; climate change adaption; disaster risk reduction; interdisciplinary collaboration